Mushroom bodies regulate habit formation in Drosophila. - Brembs, B. (Current Biology, 2009)
To make good decisions, we evaluate past choices to guide later decisions. In most situations, we have the opportunity to simultaneously learn about both the consequences of our choice (i.e., operantly) and the stimuli associated with correct or incorrect choices (i.e., classically). Interestingly, in many species, including humans, these learning processes occasionally lead to irrational decisions. An extreme case is the habitual drug user consistently administering the drug despite the negative consequences, but we all have experience with our own, less severe habits. The standard animal model employs a combination of operant and classical learning components to bring about habit formation in rodents. After extended training, these animals will press a lever even if the outcome associated with lever-pressing is no longer desired. In this study, experiments with wild-type and transgenic flies revealed that a prominent insect neuropil, the mushroom bodies (MBs), regulates habit formation in flies by inhibiting the operant learning system when a predictive stimulus is present. This inhibition enables generalization of the classical memory and prevents premature habit formation. Extended training in wild-type flies produced a phenocopy of MB-impaired flies, such that generalization was abolished and goal-directed actions were transformed into habitual responses.